Numerical areal density of CD34 and CD117 immunoreactive hematopoietic cells in human fetal and embryonic liver - Jelena Vladičić-Mašić; Ivan Nikolić; Vera Todorović; Marko Jović; Vladimir Petrović; Srđan Mašić; Nikolina Dukić; Snežana Zečević (Биомедицинска истраживања, 2019)
Introduction: Hematopoiesis is the process of developing blood cells and the formed elements of blood. This dynamic process occurs postnatally in the bone marrow, while the prenatal hematopoiesis is scattered over multiple localizations. It begins in the yolk sac, in the intra-embryonic islands of hematopoiesis, and continues in the liver, spleen, and bone marrow, as well as, according to new research, in the placenta. The liver, as the largest hematopoietic organ of intrauterine development, is the source of hematopoietic stem cells. The aim of the study was to identify and quantify hematopoietic cells in human fetal and embryonic liver showing the immunoreactivity of CD34 and CD117 molecules. Methods: 5 human embryonic livers and 25 human fetal livers, 7 to 38 weeks of gestational age, were used in the study. Liver samples were routinely processed to paraffin molds. Tissue sections, 5 µm thick, were stained with hematoxylin and eosin as immunohistochemical detection of CD34 and CD117 antigens. Quantification was performed morphometrically determining numerical areal density. The Chi-square test was used in the statistical analysis. Results: The numerical areal density of CD34 immunoreactive hematopoietic cells in the liver during the embryonic development was 0.35%: 0.30% in the first trimester (including both the embryonic and fetal period), 0.46% in the second trimester and 0.10% in the third trimester. The numerical areal densities of CD117 immunoreactive hematopoietic cells in the liver during the embryonic period were 0.28%: 0.50% in the first trimester (including both the embryonic and fetal periods), 0.11% in the second trimester and 0.09% in the third trimester. Conclusion: Fetal and embryonic liver represents a significant source of CD34 and CD117 immunoreactive hematopoietic cells.
Keywords: hematopoiesis; stem cells; fetal liver; CD34 antigen; CD117 antigen